Respuesta :

Answer:

(36.692,-6.538) or simplified (36.7,-6.5)

Step-by-step explanation:

2x-3y=93

x+5y=4

You would multiply both sides of the bottom equation by -2

-2(x+5y)=4(-2) > -2x-10y=-8

   2x-3y=93

+  -2x-10y=-8

---------------------

-13y=85

divide both sides by -13

y=-6.538

plug in y for any of the two original equations, I chose the first one

2x-3(-6.5)=93

2x+19.5=93

  -19.5     -19.5

2x=73.5

divide both sides by 2

x=36.692

Answer:

3 and -1

Step-by-step explanation:

Took the test.